The Influence of Age and Gender on Readiness of EFL Teachers in Implementing Merdeka Curriculum in Bangka Belitung Province - Ana Yuliana; James Leonard Mwakapemba; Agus Widyantoro (JEELS (Journal of English Education and Linguistics Studies), 2025)
The purpose of this study was to explore English teachers’ readiness to implement Merdeka curriculum which focused on three aspects of readiness: emotive-attitudinal, cognitive, and behavioral. It investigates whether teachers’ readiness in implementing Merdeka curriculum varies by age and gender. This study used quantitative research in the form of survey design. The samples of the study were 179 English teachers at senior and vocational high schools in Bangka Belitung Province, Indonesia. The data were collected from 68 items of the questionnaire, consisting of 26 items for emotive-attitudinal dimensions, 28 items for cognitive dimensions, and 14 items for behavioral dimensions. Descriptive statistics and MANOVA were computed and analyzed using Microsoft Excel and IBM SPSS 26.0. The findings of the study showed that all of the teachers shared a moderate level of readiness in implementing Merdeka curriculum. Teachers’ readiness in implementing Merdeka curriculum showed a statistically significant difference among different age groups of teachers. However, there was no significant difference between male and female teachers’ readiness. The findings of this study suggest that while English teachers in Bangka Belitung Province exhibit a moderate level of readiness for implementing Merdeka curriculum, their preparedness may require further support, particularly in specific dimensions of readiness. The significant differences in readiness across age groups indicate that younger and older teachers may have varying needs in terms of training and professional development.